Bacteria exposed biliary epithelium and liver B cells activate intrahepatic mait cells in an MR1-dependent manner - Jeffery, H; van Wilgenburg, B; Kurioka, A; Parekh, K; Stirling, K; Roberts, S; Dutton, E; Hunter, S; Geh, D; Braitch, M; Rajanayagam, J; Iqbal, T; et al. (Elsevier, 2015)
Mucosal-Associated Invariant T (MAIT) cells are innate-like T cells characterised by the invariant TCR-chain, Vα7.2-Jα33, and are restricted by MR1, which presents bacterial vitamin B metabolites. They are important for antibacterial immunity at mucosal sites; however, detailed characteristics of liver-infiltrating MAIT (LI-MAIT) and their role in biliary immune surveillance remain unexplored.The phenotype and intrahepatic localisation of human LI-MAIT cells was examined in diseased and normal livers. MAIT cell activation in response to E. coli-exposed macrophages, biliary epithelial cells (BEC) and liver B cells was assessed with/without anti-MR1.Intrahepatic MAIT cells predominantly localised to bile ducts in the portal tracts. Consistent with this distribution, they expressed biliary tropic chemokine receptors CCR6, CXCR6, and integrin αEβ7. LI-MAIT cells were also present in the hepatic sinusoids and possessed tissue-homing chemokine receptor CXCR3 and integrins LFA-1 and VLA-4, suggesting their recruitment via hepatic sinusoids. LI-MAIT cells were enriched in the parenchyma of acute liver failure livers compared to chronic diseased livers. LI-MAIT cells had an activated, effector memory phenotype, expressed α4β7 and receptors for IL-12, IL-18 and IL-23. Importantly, in response to E. coli-exposed macrophages, liver B cells and BEC, MAIT cells up-regulated IFN-γ and CD40 Ligand and degranulated in an MR1-dependent, cytokine-independent manner. In addition, diseased liver MAIT cells expressed T-bet and RORγt and the cytokines IFN- γ, TNF-α, and IL-17.Our findings provide the first evidence of an immune surveillance effector response for MAIT cells towards biliary epithelial cells in human liver; thus they could be manipulated for treatment of biliary disease in the future.